Optimalisasi Pemanfaatan Limbah Organik Menjadi Produk Multipurpose Cleaner Dalam Upaya Pemberdayaan Perempuan di Kel. Mojotengah, Kec.Menganti , Kota Gresik - Shinta Wurdiana Rhomadona; Meika Ayu Cahya Ningrum (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2022)
The waste generated by people's daily activities consists of organic and non-organic waste. Nearly 70% of the waste that is disposed of in landfills is organic waste, which causes an unpleasant odor and the decomposition of this organic waste can produce methane gas which is the cause of global warming. Mojotengah Village, Menganti District has potential in environmental cleanliness with the existence of a waste bank institution with the name "BS Bumi Lestari" and environmental cadres totaling 2 people per RT, but the waste bank only processes inorganic waste while organic waste still has no processing. Household organic waste will be disposed of in the TPA and will become a burden at the TPA later. Household waste can also cause environmental damage and pollution such as floods which can have a negative impact on public health. Some diseases that can be caused by this waste are diarrheal disease, dengue fever, typhus, cholera, fungal diseases, and intestinal worms. Therefore, this area actually has great potential for the development of eco-enzymes as an effort to utilize organic waste into multipurpose cleaner products, such as cleaning fluids for household furniture, detergents, body cleansers, for water purification and deodorizing, for food preservation, as insecticides and pesticides. The method of activity used is through outreach techniques, counseling, training on the use of organic waste into multipurpose cleaner products, assistance and improvement of village facilities by providing segregated waste bins, organic and inorganic to residents and the surrounding environment in an effort to empower women towards the eco-community concept, so that it has an impact towards improving environmental quality.